Clinical and Prognostic Significance of Preoperative Plasma Fibrinogen Levels in Patients with Operable Breast Cancer. - Yu Mei; Song Zhao; Xiaofei Lu; Haixia Liu; Xiangyi Li; Rong Ma (PLoS ONE, 2016)
PURPOSE:Elevated plasma fibrinogen levels are associated with tumor progression and poor outcomes in different cancer patients. The objective of this study was to investigate the clinical and prognostic value of preoperative plasma fibrinogen levels in patients with operable breast cancer. METHODS:Two hundred and twenty-three patients diagnosed with breast cancer were retrospectively evaluated in this study. Plasma fibrinogen levels were examined before treatment and analyzed along with patient clinicopathological parameters, disease-free survival (DFS) and overall survival (OS). Both univariate and multivariate analyses were performed to identify the clinicopathological parameters associated with DFS and OS. RESULTS:Elevated preoperative plasma fibrinogen levels were directly associated with age of diagnose (≤47 vs. >47, p<0.001), menopause (yes vs. no, p<0.001), tumor size (T1&T2 vs. T3&T4, p = 0.033), tumor stage (I vs. II vs. III, p = 0.034) and lymph node involvement (N = 0 vs. 1≤N≤3 vs. N≥4, p<0.001), but not with histological grade, molecular type and other Immunohistochemical parameters (ER, PR, HER2 and Ki-67). In a univariate survival analysis, tumor stage, tumor size, lymph node involvement (p<0.001/p<0.001) and plasma fibrinogen (p<0.001/p<0.001) levels were associated with disease-free and overall survival, but just lymph nodes involvement (p<0.001, hazard ratio [HR] = 2.9, 95% confidence interval [CI] = 1.6-5.3/p = 0.006, HR = 3.2, 95% CI = 1.4-7.3) and plasma fibrinogen levels (p = 0.006, HR = 3.4, 95% CI = 1.4-8.3/p = 0.002, HR = 10.1, 95% CI = 2.3-44.6) were associated with disease-free and overall survival in a multivariate survival analysis, respectively. CONCLUSIONS:This study demonstrates that elevated preoperative plasma fibrinogen levels are associated with breast cancer progression and are independently associated with a poor prognosis in patients with operable breast cancer.